Indicadores de acessibilidade para o planejamento do transporte público em cidades paulistas de médio porte - Zacharias, Leandro Neves (Universidade Federal de São Carlos, 2021)
Accessibility studies have gained relevance in urban planning as they relate land use with transport systems, especially transit. However, these studies focus on metropolitan regions and large cities due to government preferences and data availability. Even with the relevance of medium-sized cities in the urban network, there are knowledge gaps about accessibility in urban profile. The work aims to evaluate transit accessibility in medium-sized cities. The cities of Araraquara, Bauru, Catanduva, Limeira and São Carlos were chosen based on their population level and the transit data avaliability. Two accessibility indicators were used. The location-based accessibility indicators assessed the percentage of opportunities reached in a 30-minute transit trip. The infrastructure-based accessibility measured the percentage of opportunities close to boarding points. Both indicators revealed a pattern that accessibility in medium-sized cities reaches high values for a large part of the urban area. However, there are peripheric regions where accessibility is drastically lower, showing an inequality of access to opportunities. These inequalities are due to transit network organization and the opportunities concentration in central regions. Still, the effect of the territorial dimension and the lesser details of the data can interfere in the indicator results. The study established the need to assess accessibility in medium-sized cities, so that the continuity of the research is very important to consolidate the indicators well suited to the reality of this very important city profile in urban network.
Accessibility indicators for public transport planning in medium-sized cities in Sao Paulo state
Keywords: Acessibilidade; Indicadores; Cidades de médio porte; Planejamento de transportes; Transporte público; Uso do solo; Accessibility; Indicators; Medium-sized cities; Transport planning; Transit; Land-use; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES; ENGENHARIAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO::PLANEJAMENTO E PROJETO DO ESPACO URBANO